Experimental Study on Slag Discharge of Sandstone in Small-Angle Reverse Drilling and Reaming - Jianguang Niu, Chunyan Gao, Dongyang Geng, Yongqiang Shi, Xiufeng Liang (Forest Chemicals Review, 2021)
When oil and gas pipelines cross mountains, reverse drilling is adopted, and rock slag formed by drilling falls by its weight. Under the construction condition of small-angle reverse well drilling, the rock slag cannot fall by its weight when the drill bit reams. Based on the analysis of small-angle reverse well drilling for oil and gas pipeline crossing the mountain, a slag discharge test device is designed, and the slag discharge effect is tested from four angles of 20°, 25°, 30°, and 35°. Combined with the actual construction conditions, 2.5m3/h, 5m3/h, and 10m3/h water flow is used to assist slag removal, to approximately simulate the process of rock slag falling from the broken rock surface during drilling with small-angle reverse drilling. At the same time, the velocity of rock slag was monitored during the experiment, and the kinematic characteristics and mechanism of rock slag falling were analyzed. The research shows that when the stability coefficient k of sandstone slag is less than 0.7, the slag can be fully discharged, and the starting speed can be calculated by using the improved formula of Stirling. Under the condition of 20-35°, the critical start-up speed of slag-carrying water flow under different displacement is in the range of 0-5m/s; When the drilling angle of the reverse well is 20° or above, the sandstone slag has an obvious slag removal effect with the aid of water flow of 10 m3/h. When the whole angle of the reverse well is 30° or above, the sandstone slag has an obvious slag removal effect with the aid of 5m3/h water flow. The research of small-angle anti-drilling in oil and gas pipeline crossing mountains is an innovation in the construction technology of oil and gas pipeline crossing mountains, which is not only conducive to promoting the progress of oil and gas pipeline construction technology. It can also provide a reference for the research of construction technology in other areas of oil and gas pipelines and has important research significance.